Optimization of Remote Sensing Data In Monitoring Morphology Change of Siak River in Pekanbaru City - Eggy Arya Giofandi; Dhanu Sekarjati; Dhia`ul Hayat; Cipta Estri Sekarrini; Iswandi Umar (Jurusan Teknik Lingkungan, FTM, Universitas Pembangunan Nasional â€œVeteranâ€ Yogyakarta, 2022)
River condition that experiences change is not apart from the utilization of river boarder for human life needs. Beside the effect of built land development, river morphology changes because of erotion and deposition. Therefore, it needs detection of river morphology change, one of which is by utilizing remote sensing data with Modification Normalized Difference Water Index. Modification Normalized Difference Water Index can separate between water and land sharply until river morphology analysis can be clearer. This research aims to detect the change of Siak River morphology in Pekanbaru City caused by abrasion and deposition by using Modification of Normalized Difference Water Index on landsat temporal data of 2008 and 2018. Data used in this research were Landsat 7 image of 2008 and Landsat 8 year of 2018. The research results show that morphology changes of Siak River in Pekanbaru City is caused by erotion and deposition. The erotion area reaches 12.133 ha and deposition 4.488 ha in the period of 10 years